The bird book : the stories, science, and history of birds - Pitts, Gill; Hume, Rob (Dorling Kindersley Limited, 2024)
"Birds are dinosaurs with a history going back millions of years. Our fascination with them runs deep in history, and our close association is reflected in creation stories, myths, legends, songs, and children's stories"--Amazon.com.